Happiness Curriculum and Education of Students of Class VIII from Schools of Delhi - Khan, Aerum; Singh, Alka (Voices of Teachers and Teacher Educators, 2023)
A more all-encompassing approach to education that prioritises student well-being in addition to academic performance has gained popularity in recent times (Coulombe, et.al. 2021). Several educational initiatives and programmes from throughout the globe reflect this transformation. For instance, ’ensure inclusive and equitable quality education and promote lifelong learning opportunities for all’ (https://sdgs.un.org/goals), with a focus on promoting well-being and happiness, is the fourth goal among seventeen of the Sustainable Development Goals (SDG) of the United Nations. On the contrary, the mainstream media frequently focuses on incidents of depression and suicide among students due to exam failure and quantitative evaluation. The purpose of this research is to examine how the happiness curriculum supports the fourth Sustainable Development Goal (SDG) for quality education. It was introduced in Delhi’s state government schools in July 2018. It inquires as to whether or not pupils are able to communicate their feelings and manage their academic stress. This pilot study is intending to measure the effectiveness of the Happiness Curriculum in reducing stress and increasing the student participation in classroom activities of the students of Class VIII.